Remote Work In The Time of The COVID-19 Pandemic In Poland - Michał Trziszka (Communications of International Proceedings, 2021)
The aim of the article is to present the aspects of teleworking in Poland as an alternative to stationary work in the social and organizational dimension, especially in the situation of forced lockdown caused by the COVID-19 coronavirus pandemic, which began in Poland in March 2020. In the era of rapid technology development and changes on the market work for the benefit of the employee and the enterprise, remote work in many industries has turned out to be a recipe for survival. In addition to the positive aspects of teleworking as a flexible approach to performing professional duties - place, time and freedom of action, home work also brings negative psychological and social effects, the most common of which are: a sense of isolation and blurring the boundary between work and private life. The author indicates the strengths and weaknesses of teleworking, illustrating them with the results of research conducted among employees of various industries, which, as a result of the COVID-19 pandemic, used the remote working model.
Keywords: remote work; COVID-19; work organization; remote management; lockdown; remote worker; work organization; pandemic.